Technology Assisted Arabic Language Learning through the Wayground Application at Nahdlatul Ulama University of Purwokerto - Lina Husnul Karimah; Nida Farhani Mubarokah (Darul Yasin Al Sys, 2026)
Although technology-assisted Arabic language learning has attracted increasing scholarly attention, research specifically examining the use of the Wayground application to support Arabic grammar learning in higher education remains limited. This study aimed to explore the implementation of the Wayground application in Arabic language learning and its contribution to improving students’ understanding of Arabic grammar at Nahdlatul Ulama University of Purwokerto. A qualitative approach was employed using a descriptive case study design. Data were collected through classroom observations, semi-structured interviews, and documentation, and were analyzed using thematic analysis. The findings indicate that the use of the Wayground application increased students’ engagement, supported interactive learning, and facilitated a clearer understanding of Arabic grammar concepts through technology-based activities. These findings contribute to the theoretical development of technology-enhanced language learning and broaden understanding of digital media integration in Arabic language education. The study concludes that the Wayground application plays an important role in fostering an engaging and effective Arabic language learning environment and recommends the integration of technology-based platforms to strengthen grammar instruction in higher education. The study further offers practical implications for optimizing digital learning tools and highlights the need for future research on the long-term effects of digital applications on Arabic language proficiency and learning outcomes.